Multifaceted roles of SARM1 in axon degeneration and signaling - Waller, Thomas J.; Collins, Catherine A. (Frontiers in Cellular Neuroscience, 2022)
Axons are considered to be uniquely vulnerable components of the nervous system; impairments to a neuron’s axon leads to an effective silencing of a neuron’s ability to communicate with other cells. Nervous systems have therefore evolved plasticity mechanisms for adapting to axonal damage. These include acute mechanisms that promote the degeneration and clearance of damaged axons and, in some cases, the initiation of new axonal growth and synapse formation to rebuild lost connections. In addition, neurons that experience injury or stressful conditions can change their excitability and resilience to damage, such that neurons that experienced a previous ‘conditioning’ injury have an altered likelihood to degenerate and regenerate. MAP Kinase signaling pathways that detect axonal damage and stress play critical roles in orchestrating both the degeneration and regeneration of axons, as well as the death or survival of the neuron. Work over the past decade has revealed critical roles for the Sarm1 NADase enzyme in promoting axonal degeneration and cell death in the nervous system. Here we will consider the multiple intersections between Sarm1 and the injury signaling pathways that coordinate cellular adaptations to nervous system damage.